PELATIHAN MENJAHIT TINGKAT 1 DALAM MENUMBUHKAN MOTIVASI WIRAUSAHA DI SEKOLAH MODEVAK KENCANA KABUPATEN PONOROGO - Ela Khoirotul Qomariyah; Ketut Atmaja (JPUS: Jurnal Pendidikan Untuk Semua, 2020)
This research b Level 1 sewing training is one of the programs aimed at housewives and young women in order to become productive people, to provide participants with skills in the form of livelihoods that can be used as entrepreneurship, which is one way to reduce unemployment.  This study aims to analyze about: (1) Implementation of level 1 sewing training; (2) Entrepreneur motivation for level 1 sewing training participants; (3) Implementation of level 1 sewing training that is able to foster entrepreneurial motivation for training participants.This study uses a qualitative approach, research subjects include two instructors and four training participants sewing level 1. Data collection techniques used observation, interviews, and documentation, as well as using data analysis techniques with data reduction, data presentation, and drawing conclusions.The results of this study were the first level sewing training carried out in the Kencana Modevak School running according to the procedure and was successful, as evidenced after attending the training the trainees had entrepreneurial motivation such as high interest, seriousness and commitment in preparing for entrepreneurs. As well as in fostering entrepreneurial motivation, trainers trainers use 4 ways, they are given material about entrepreneurship, given the opportunity to leave their clothes at the Kencana boutique, mentoring after graduation in the form of free consultations, and given communication facilities in the form of grup whatsapp for each other offer order..